Psychiatry : A Very Short Introduction - Burns, Tom (New York Oxford University Press, 2018)
What is psychiatry? -- Asylums and the origins of psychiatry -- The move into the community -- Psychoanalysis and psychotherapy -- Psychiatry under attack - inside and out -- Open to abuse -- Into the 21st century.
Include Illustrations and Index
Keywords: Psychiatry -- Clinical psychology